TONSILLITIS: A COMPLETE MEDICAL GUIDE (Homoeopathy for All, 2025)
The term "Tonsillitis" is derived from a combination of two Latin words namely "Tonsillae" and "itis" which refers to palatine tonsil and inflammation respectively. It is also commonly called as the "Sore Throat". Tonsillitis, as the name suggests, is the inflammation of the tonsils, which are a pair oflymphoid tissue present at the back of the throat on the either side. They are also a vital component of the immune system and act as a first line of defense for protecting the human body against inhaled pathogens. Tonsillitis sometimes can even extend to other regions of the mouth and are termed as Tonsillopharyngitis (pharynx is infected) and Adenotonsillitis (adenoids are infected).Tonsillitis is most commonly observed in children and young adults but can occur in any age group. It is primarily caused by bacterial or viral agents. Viruses such as adenovirus, rhinovirus, influenza, coronavirus, and respiratory syncytial virus and bacteria such as Group A beta-hemolytic streptococcus (GABHS), Staphylococcus aureus, Streptococcus pneumoniae, Mycoplasma pneu moni ae, and Chlamydia pneumonia are some species triggering Tonsillitihumans. Tonsillitis is considered to be contagious and can spread from one person to another with the help of airborne droplets released by coughing orsneezmg.
Keywords: inflammatory; Tonsillitis; NSAIDs; AAFP